Epigenetic regulation of bone remodeling and its role in the pathogenesis of primary osteoporosis - B. I. Yalaev; R. I. Khusainova (Вавиловский журнал генетики и селекции)
Discovery of molecular mechanisms of primary osteoporosis development is fundamental to understand the pathogenesis of musculoskeletal diseases in general and for identifying key links in the genetic and epigenetic regulation of bone remodelling genes. The number of identified molecular genetic markers for osteoporosis is increasing but there is a need to describe their functional interactions. These interactions have been determined to be associated with the control of expression of a number of transcription factors and the differentiation of mesenchymal stem cells through the pathway of osteoblastogenesis or adipogenesis, and monocytic precursors through the pathway of osteoclastogenesis. The results of epigenetic studies have significantly increased the understanding of the role of post-translational modifications of histones, DNA methylation and RNA interference in the osteoporosis pathogenesis and in bone remodelling. However, the knowledge should be systematised and generalised according to the results of research on the role of epigenetic modifiers in the development of osteoporosis, and the influence of each epigenetic mechanism on the individual links of bone remodelling during ontogenesis of humans in general, including the elderly, should be described. Understanding which mechanisms and systems are involved in the development of this nosology is of interest for the development of targeted therapies, as the possibility of using microRNAs to regulate genes is now being considered. Systematisation of these data is important to investigate the differences in epigenetic marker arrays by race and ethnicity. The review article analyses references to relevant reviews and original articles, classifies information on current advances in the study of epigenetic mechanisms in osteoporosis and reviews the results of studies of epigenetic mechanisms on individual links of bone remodelling.